MiR-890 inhibits proliferation and invasion and induces apoptosis in triple-negative breast cancer cells by targeting CD147 - Wang, Cheng (BMC Cancer, 2019)
BACKGROUND: Triple-negative breast cancer (TNBC) is a type of breast cancer with a high degree of malignancy. Because of the remarkable biological characteristics of high invasion, metastasis and recurrence, TNBC is often accompanied by a poor prognosis. As a molecular characteristic of TNBC, high expression of CD147 has been confirmed by a large number of studies. However, the mechanism of CD147 expression regulation in TNBC remains elusive. In this study, we investigated the roles of miR-890 in inhibiting CD147. METHODS: Quantitative Reverse Transcription-Polymerase Chain Reaction (qRT-PCR) was used to detect CD147 mRNA and miR-890 level, and western blotting was used to detect CD147 protein. Bioinformatics screening and 3′-Untranslated Region (3′-UTR) luciferase assays were used to analyze the microRNAs (miRNA) binding site. Cell proliferation, apoptosis and invasion were assessed by using CCK-8, flow cytometry and transwell assays. RESULTS: The upregulation of miR-890 inhibited cell proliferation and invasion, induced apoptosis in MDA-MB-231 and HCC-70 TNBC cells by negatively regulating its target gene, CD147, and the upregulation of CD147 rescued the inhibitory effects of miR-890. miR-890 targeted CD147 by binding to its 3′-UTR. Further results showed that the upregulation of miR-890 also inhibited the expression of MMPs, the downstream genes of CD147, and promoted the cleavage of Caspase-3. The CD147 recovery experiment was further confirmed by the activity changes in the downstream MMPs of CD147. In addition, it was confirmed that the effect of CD147 in promoting TNBC cell proliferation and invasion, inhibiting apoptosis was related to the change in caspase-3 activity. CONCLUSION: The downregulation of miR-890 is the potential cause of high CD147 expression in TNBC, which can promote the malignant transformation of TNBC.